Acquired diaphragmatic hernia following a peritoneal biopsy for gastric cancer dissemination in the diaphragm: a case report - Kazuya Endo; Kentaro Hara; Koichi Nemoto; Nozomi Goto; Kazuhisa Nishina; Nozomi Funatsu; Maki Takagi; Kohdai Ueno; Atsushi Onodera; Haruhiko Cho (Surgical Case Reports, 2023)
Abstract Background Acute diaphragmatic hernia is a life-threatening condition caused by prolapse of an abdominal organ into the thoracic cavity through a defect in the diaphragm. We present herein a case of acquired diaphragmatic hernia following a peritoneal biopsy for gastric cancer dissemination in the diaphragm. Case presentation A 72-year-old, female patient presented with a complaint of acute abdomen 10 months after receiving a diagnosis of stage IV gastric cancer with peritoneal dissemination based on peritoneal biopsy findings during staging laparoscopy. Computed tomography demonstrated herniation of the small intestine into the thoracic cavity. Emergency surgery was performed, and a full-thickness diaphragmatic defect was found intraoperatively at the same location as the previous, peritoneal biopsy. The incarcerated small intestine was atraumatically repositioned into the abdominal cavity, and the defect was closed laparoscopically using an absorbable barbed suture. Conclusions Although complications of staging laparoscopy are extremely rare, excising disseminated nodules from the diaphragm carries the risk of diaphragmatic hernia. For this reason, avoiding excision is desirable unless a diaphragmatic biopsy is needed.